Parenostres en substitució de Salms: a propòsit d'un text català del segle XV - Olivar, Alexandre (Miscel·lània litúrgica catalana, 2005)
The Grey Collection codex, MS 3.0.5. from the Cape Town, South Africa, National Library, a 15th century book of hours from Italy, contains at its end a page in Catalan dating from the same time. It is a table indicating the number of Lord?s Prayers to be recited at each canonical hour by those replacing the Psalms of the divine office by the Lord?s Prayer. Since there is no systematic study of this usage practised from the Middle Ages until the present day, the author compares this text with some other sources.